2006
DOI: 10.1152/ajpendo.00487.2005
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol, a red wine antioxidant, possesses an insulin-like effect in streptozotocin-induced diabetic rats

Abstract: Aberrant energy metabolism is one characteristic of diabetes mellitus (DM). Two types of DM have been identified, type 1 and type 2. Most of type 2 DM patients eventually become insulin dependent because insulin secretion by the islets of Langerhans becomes exhausted. In the present study, we show that resveratrol (3,5,4'-trihydroxylstilbene) possesses hypoglycemic and hypolipidemic effects in streptozotocin-induced DM (STZ-DM) rats. In resveratrol-treated STZ-DM rats, the plasma glucose concentration on day 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
238
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 340 publications
(256 citation statements)
references
References 45 publications
16
238
1
1
Order By: Relevance
“…It has been reported that the oral administration of RSV reduced the blood glucose, plasma lipid and free fatty acid levels in a spontaneous diabetic model [29] .…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that the oral administration of RSV reduced the blood glucose, plasma lipid and free fatty acid levels in a spontaneous diabetic model [29] .…”
Section: Discussionmentioning
confidence: 97%
“…Recently, the direct inhibitory effect of resveratrol on insulin secretion from pancreatic islets of normal rats was described [18][19][20]. Resveratrol was also found to affect blood insulin concentrations [20][21][22][23] and to exert an insulin-like effect in diabetic rats [21,23]. The other beneficial effects of resveratrol, including enhanced glucose uptake by soleus muscle, hepatocytes and adipocytes [21] and the decreased blood glucose and glycosylated haemoglobin, were demonstrated in diabetic rats [24].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that RSV has a wide variety of benefits in preventing illnesses such as cardiovascular disease and ischemic injuries, cancer, and in prolonging the lifespan of various organisms [7][8][9][10]. One report revealed that RSV has antihyperglycemic and antihypertriglyceridemic effects in diabetic rats [11]. Although the beneficial effects of RSV on glucose homeostasis have been reported, it is unknown whether RSV has a protective effect against β-cell-specific cytotoxic agents.…”
mentioning
confidence: 99%